Efficacy of azithromycin combined with intravenous immunoglobulin in the treatment of refractory mycoplasma pneumoniae pneumonia in children: a meta-analysis - Yuan-yuan Shen; Zi-qiang Feng; Zhong-ping Wang; Xue-qin Wang; Cheng Luo; Qing-zhong Liu (BMC, 2024)
Abstract Background The incidence of refractory Mycoplasma pneumoniae pneumonia (RMPP) in children is increasing, posing a serious threat to life safety. Intravenous immunoglobulin (IVIG) has demonstrated the ability to modulate the immune system and has shown the potential to treat RMPP. This study evaluated the clinical efficacy and safety of azithromycin combined with IVIG in the treatment of RMPP in children through a meta-analysis. Methods A comprehensive search was conducted in seven databases including PubMed and Cochrane Library, and the studies on the treatment of RMPP in children with azithromycin combined with IVIG were screened. After data extraction, meta-analysis and sensitivity analysis were performed to assess heterogeneity and stability. Results Thirteen randomized controlled trials and two cohort studies were included, totaling 1,142 children. The results of meta-analysis showed a higher clinical efficacy rate (RR = 1.18, 95% CI: 1.11-1.25, P < 0.01) and shorter time to defervescence (MD = -2.12, 95% CI: -2.69--1.55), time to disappearance of pulmonary rales (MD = -2.90, 95% CI: -3.57--2.23), time to disappearance of cough (MD = -3.59, 95% CI: -4.51--2.67), and hospital length of stay (MD = -5.72, 95% CI: -8.80--2.64) in the experimental group receiving azithromycin combined with IVIG treatment compared to the control group treated with azithromycin alone. Additionally, there was no significant publication bias in this meta-analysis. Conclusion Treatment with azithromycin combined with IVIG is more effective than treatment with azithromycin alone for children with RMPP. Clinical trial number Not applicable.